2016
DOI: 10.3345/kjp.2016.59.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous levetiracetam versus phenobarbital in children with status epilepticus or acute repetitive seizures

Abstract: PurposeThis study compared the efficacy and tolerability of intravenous (i.v.) phenobarbital (PHB) and i.v. levetiracetam (LEV) in children with status epilepticus (SE) or acute repetitive seizure (ARS).MethodsThe medical records of children (age range, 1 month to 15 years) treated with i.v. PHB or LEV for SE or ARS at our single tertiary center were retrospectively reviewed. Seizure termination was defined as seizure cessation within 30 minutes of infusion completion and no recurrence within 24 hours. Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
5
0
4
Order By: Relevance
“…AED therapy was changed from Phenobarbitone to Levetiracetam by the physician. This is in reference to the study by Lee YJ which states that Levetiracetam is efficacious than Phenobarbitone in children with status epilepticus or acute repetitive seizure [10].…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 91%
“…AED therapy was changed from Phenobarbitone to Levetiracetam by the physician. This is in reference to the study by Lee YJ which states that Levetiracetam is efficacious than Phenobarbitone in children with status epilepticus or acute repetitive seizure [10].…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 91%
“…Anfallsbeendigung innerhalb von 10 Minuten nach Infusion und kein Wiederauftreten innerhalb von 24 Stunden GTKSE (n = 4) 75%NKSE (n = 2) 100% [11] Nach Beginn der Levetiracetam-Infusion NKSE (n = 1) 100% [12] Anfallsbeendigung 30 Minuten nach Infusionsbeginn GTKSE (n = 20)FMSE (n = 2) gesamt 59,1% [13] Anfallsbeendigung 30 Minuten nach Infusionsende und keine Anhaltpunkte für weitere Anfallsaktivität innerhalb der nächsten 24 Stunden GTKSE (n = 50) 78%unklar (n = 12) 33,3% [14,15] Anfallsbeendigung 30 Minuten nach Infusionsbeginn und kein Wiederauftreten innerhalb der nächsten 12 Stunden NKSE (n = 30) <40% a [16] Anfallsbeendigung 30 Minuten nach der Infusion und kein Wiederauftreten innerhalb der nächsten 6 Stunden GTKSE (n = 18) 44,4% [17] "wenige" Stunden nach erster LEV-Gabe EPC (n = 1) 100% [18] Verhaltensänderung und EEG-Veränderung im Verlauf von 2 Monaten NKSE (n = 1) 100% [19] "zeitlicher Zusammenhang" mit Levetiracetam-Infusion GTKSE / NKSE/ARS (n = 70) 83% [20] Clonazepam Davon konnten eine ungarische [37] und zwei japanische [27,42] Arbeiten lediglich nach den Abstracts ausgewertet werden. Die Patientenbeschreibungen, Dosierungen der LEV-Gabe und die Behandlungserfolge sind in ▶Tab.…”
Section: Literaturunclassified
“…In einer prospektiven Vergleichsstudie zwischen Phenytoin, Valproat und LEV beim generalisierten tonisch klonischen Status epilepticus (GTKSE) nach erster Lorazepamgabe mit 50 Patienten in jedem Behandlungsarm kam es ausschließlich bei drei mit LEV behandelten Patienten zu einer postiktalen Psychose [14]. In einer pädiatrischen Serie kam es bei 38 LEV Anwendungen (12 SE, 26 Anfallsserien) viermal zu aggressivem Verhalten und einmalig zu Erbrechen [15]. Vorübergehende Erregung wurde auch bei zwei von 60 wegen SE oder Anfallsserien mit LEV behandelten Patienten berichtet [48].…”
Section: Nebenwirkungenunclassified
See 1 more Smart Citation
“…There are also case series that report the use of newer AEDs with IV formulations, eg LEV. [15][16][17][18][19][20][21][22] Despite the lack of good randomised controlled trials, in a recent meta-analysis, the uses of IV lacosamide, LEV, VPA, phenytoin, and phenobarbital were compared. It found that LEV, VPA, and phenobarbital were comparable in terms of efficacy in stopping benzodiazepine-resistant SE.…”
Section: Established Status Epilepticusmentioning
confidence: 99%